2021
DOI: 10.1016/j.wneu.2020.11.133
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Coronavirus Disease 2019 (COVID-19) Incidence and Outcomes in Neurosurgical Patients at Two Tertiary Care Centers in Washington, DC, During a Pandemic: A 6-Month Follow-up

Abstract: Objective Coronavirus disease 2019 (COVID-19) continues to affect all aspects of healthcare delivery and neurosurgical practices are not immune to its impact. We aim to evaluate neurosurgical practice patterns as well as perioperative incidence of COVID-19 in neurosurgical patients and their outcomes. Methods A retrospective review of neurosurgical and neurointerventional cases at two tertiary centers during the first three months of the first peak of COVID-19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…Eight studies reported the case volume of elective neurosurgical procedures performed both before and during the COVID-19 pandemic. [ 27 , [37] , [38] , [39] , [40] , 47 , 50 , 54 ] Collectively, the number of elective surgeries decreased by 70.4% (OR=0.296, 95% CI 0.210–0.418, p <0.001) ( Figure 2 A). A comparison of non-elective neurosurgical procedures was reported in 9 studies, with an overall decrease of 68.2% (OR=0.318, 95% CI 0.193–0.525, p <0.001) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies reported the case volume of elective neurosurgical procedures performed both before and during the COVID-19 pandemic. [ 27 , [37] , [38] , [39] , [40] , 47 , 50 , 54 ] Collectively, the number of elective surgeries decreased by 70.4% (OR=0.296, 95% CI 0.210–0.418, p <0.001) ( Figure 2 A). A comparison of non-elective neurosurgical procedures was reported in 9 studies, with an overall decrease of 68.2% (OR=0.318, 95% CI 0.193–0.525, p <0.001) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, 935 articles were left; their titles and abstracts were screened, and 78 relevant articles were identified for full-text review. Overall, this study collated data and information from 49 articles, [ 11 , 12 , 17 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] with 25 of them included in the quantitative synthesis ( Figure 1 ). Twenty-two of these articles were retrospective in nature, two had data collected both retrospectively and prospectively, one was both a retrospective cohort study and a survey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it was observed that incidence rates remain low despite the increase in the volume of patients, which supports the effectiveness of general and specialized measures adopted in the different centers to minimize the spread of this disease. 1 We thank Sarpong et al. 1 for providing this valuable information.…”
mentioning
confidence: 96%
“…We read with great interest the article published in your respected journal by Sarpong et al. 1 entitled “Perioperative COVID-19 Incidence and Outcomes in Neurosurgical Patients at Two Tertiary Care Centers in Washington, DC, During a Pandemic: A 6-month Follow-up,” where the authors evaluated the perioperative incidence of coronavirus disease 2019 (COVID-19) in neurosurgery patients, as well as their respective evolution. During their study, they obtained a perioperative incidence of COVID-19 of 5.4% at the peak of the pandemic and 2.9% in the postpeak period.…”
mentioning
confidence: 99%